2019
DOI: 10.3390/polym11050895
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel pH-Tunable Thermoresponsive Hydroxyl-Terminated Hyperbranched Polyether

Abstract: In this study, a new pH-tunable thermoresponsive hydroxyl-terminated hyperbranched polyether (HTHP 2) was successfully prepared via a one-pot cationic polymerization technique and postmodification. In the first step, hydroxyl-terminated hyperbranched polyether containing double bonds (HTHP 1) were synthesized. Then, through thiol-ene “click” reaction, pH-responsive carboxyl groups were introduced to the target polymer of HTHP 2. The products were characterized via Fourier-transform infrared spectra (FTIR), nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…42,43 Fan et al reported a hyperbranched polyether with thermo-and pH-responsiveness via "one-pot" cationic SCROP. 38 In an early study, Zhuo et al adopted the idea of SCROP for the preparation of a PEGattached multiarm aliphatic HBPC, which showed high micellar stability, a high doxorubicin loading content, and sustained release properties. 32 By exploiting a similar strategy, Parzuchowski and coworkers have developed a fluorinated HBPC and investigated its solubility in carbon dioxide.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Fan et al reported a hyperbranched polyether with thermo-and pH-responsiveness via "one-pot" cationic SCROP. 38 In an early study, Zhuo et al adopted the idea of SCROP for the preparation of a PEGattached multiarm aliphatic HBPC, which showed high micellar stability, a high doxorubicin loading content, and sustained release properties. 32 By exploiting a similar strategy, Parzuchowski and coworkers have developed a fluorinated HBPC and investigated its solubility in carbon dioxide.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sun et al described the synthesis of hyperbranched polycarbonates (HBPCs) by a one-pot “A 2 +B 3 ” condensation polymerization of triols with dimethyl carbonate (DMC) . Furthermore, the self-condensing ring-opening polymerization (SCROP) of hydroxyl-terminated cyclic monomers is one of the most investigated strategies to straightforwardly access HBPs, especially for hyperbranched polycarbonates, polyethers, polyesters, , and polyphosphoesters. , Fan et al reported a hyperbranched polyether with thermo- and pH-responsiveness via “one-pot” cationic SCROP . In an early study, Zhuo et al adopted the idea of SCROP for the preparation of a PEG-attached multiarm aliphatic HBPC, which showed high micellar stability, a high doxorubicin loading content, and sustained release properties .…”
Section: Introductionmentioning
confidence: 99%